Design of a roadside observation survey for measuring occupant behaviour and vehicle type characteristics - Clark, Belinda; Monash University. Accident Research Centre (Clayton, Vic. : Monash University Accident Research Centre, 2009)
Exploration into current road safety data collection in Victoria has revealed a gap in the collection of data on behaviours revealed through roadside observation surveys. The Baseline Research Program Committee funded this project to design a roadside observation survey. The design was based on earlier benchmark of safety surveys, conducted by MUARC in 2001 and modified to accommodate new variables and updated information. This survey design proposes a sound sampling framework that can be adapted to suit small or large scale research. Data observation forms are specifically designed to collect data on: vehicle information, driver and passenger characteristics, the presence and fitting of bull-bars, the use of mobile phones while driving, motorcyclist and bicyclist characteristics, and child restraint wearing. Roadside data collection procedures have been outlined and a detailed staff training manual has been included. While the survey is designed to enable the collection of single behaviour observations it is recommended that as much data as possible is collected for the overall benefit of road safety research. Ideally inter-agency collaboration would enable regular large scale surveys to be conducted and thus bridge the current gaps in Victorian road safety data.
"November, 2009".
Title from title screen (viewed on August 23, 2010).
Bibliography: p. 21.
Text and graphics.
Mode of access: Internet via World Wide Web. Available at: http://www.monash.edu.au/muarc/reports/muarc288.html.
System requirements: Adobe Acrobat reader to view pdf files.
Keywords: Traffic safety -- Victoria; Traffic surveys -- Victoria